2021
DOI: 10.1039/d0cc06717b
|View full text |Cite
|
Sign up to set email alerts
|

A twin-axial pseudorotaxane for phosphorescence cell imaging

Abstract: A twin-axial pseudorotaxane is constructed using a phenylpyridine salt with diethanolamine (DA-PY) and cucurbit[8]uril (CB[8]), and it not only displays phosphorescence in aqueous solution but it can also be used for targeted cell-imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…Diethanolamine-modified phenylpyridine formed twin-axial pseudorotax-ane after binding with CB [8]. 37 Because of the "head-to-tail" binding form and hydrogen bond between diethanol amine and CB [8], the distance between Br and OC was drawn close, and this promoted the formation of the halogen bond (Figure 5a). Furthermore, the cooperative effect of the host's rigid cavity and blocking of diethanol amine further protected the assembly from water.…”
Section: Phosphorescence In Aqueous Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diethanolamine-modified phenylpyridine formed twin-axial pseudorotax-ane after binding with CB [8]. 37 Because of the "head-to-tail" binding form and hydrogen bond between diethanol amine and CB [8], the distance between Br and OC was drawn close, and this promoted the formation of the halogen bond (Figure 5a). Furthermore, the cooperative effect of the host's rigid cavity and blocking of diethanol amine further protected the assembly from water.…”
Section: Phosphorescence In Aqueous Solutionmentioning
confidence: 99%
“…In addition to constructing nanoparticles, supramolecular assembly was utilized to enhance the intermolecular interaction between phosphors and then facilitate phosphorescence. Diethanol­amine-modified phenylpyridine formed twin-axial pseudorotaxane after binding with CB[8] . Because of the “head-to-tail” binding form and hydrogen bond between diethanol amine and CB[8], the distance between Br and OC was drawn close, and this promoted the formation of the halogen bond (Figure a).…”
Section: Macrocycles Enhance Guest’s Phosphorescencementioning
confidence: 99%
See 1 more Smart Citation
“…50,51 Based on the above advantages, many efforts have contributed to the application of supramolecular macrocycles in purely organic RTP systems. 52–54 Tian and co-workers reported an approach to achieve amorphous purely organic RTP small molecules by modifying different phosphors onto β-cyclodextrin, which could suppress the non-radiative relaxation via intermolecular hydrogen bonding. 41 Recently, we reported that by modifying bromophenylpyridinium on hyaluronic acid and co-assembling with cucurbit[8]uril ( CB[8] ), a type of macrocycle formed by the polymerization of glycoluril and formaldehyde, 55,56 the resultant supramolecular assembly exhibited good RTP behavior in aqueous solution, which was successfully applied to mitochondrial-targeted imaging of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] Recently, we reported cucurbit[n]uril‐mediated ( n = 6–8) supramolecular phosphorescence assembly with long lifetime or high phosphorescence quantum yield. [ 5–8 ] However, controllable phosphorescence material remains a formidable challenge. It is well‐known that diarylethene derivatives could reversibly convert between two thermal stable isomers upon light irradiation.…”
Section: Introductionmentioning
confidence: 99%